2000
DOI: 10.1002/1097-0142(20000815)89:4<817::aid-cncr14>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

ICI 182,780 (Faslodex?)

Abstract: BACKGROUND The nonsteroidal antiestrogen tamoxifen is well established as an effective treatment for patients with breast carcinoma, both for the treatment of metastatic disease and as an adjuvant to surgery for patients with primary breast carcinoma. In addition to exerting antagonistic effects on the estrogen receptor, tamoxifen and its derivatives act as partial agonists on certain tissues. These agonistic effects, for example, endometrial stimulation and stimulation of tumor growth after previous response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(78 citation statements)
references
References 57 publications
5
72
0
1
Order By: Relevance
“…In our in vivo model of tamoxifen resistance we also found that AZD8931 in combination with tamoxifen significantly slowed growth. Fulvestrant alone also significantly slowed tamoxifen- resistant tumor growth in vivo as has been previously shown [42]. This suggests that in tamoxifen-resistant breast cancer cells, ER still plays a role in promoting growth, As previously shown, increased HER signaling can either modify ER activity to promote endocrine resistance [5, 29], or can promote additional alternative signaling to bypass ER [43].…”
Section: Discussionsupporting
confidence: 56%
“…In our in vivo model of tamoxifen resistance we also found that AZD8931 in combination with tamoxifen significantly slowed growth. Fulvestrant alone also significantly slowed tamoxifen- resistant tumor growth in vivo as has been previously shown [42]. This suggests that in tamoxifen-resistant breast cancer cells, ER still plays a role in promoting growth, As previously shown, increased HER signaling can either modify ER activity to promote endocrine resistance [5, 29], or can promote additional alternative signaling to bypass ER [43].…”
Section: Discussionsupporting
confidence: 56%
“…ICI 182,780 (Faslodex) from AstraZeneca (Cheshire, United Kingdom) is considered as a pure steroidal estrogen antagonist that was designed to be devoid of estrogen agonist action in both in vivo and in vitro models [41,42]. It can abolish estrogen agonist activity by competing with endogenous estrogen for ERs presented in the nuclei of estrogen responsive tissues [41,42]. As Figure  6B, E and Figure  6B, F shown, the expressions of ER-α (P < 0.05) and ER-β (P < 0.01) were blocked by ICI 182,780.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, the TAM-ER dimer binds to DNA at palindromic ERE sequences in the promoter region of E2 responsive genes. Transcription of the E2 responsive gene(s) is attenuated because the AF2, ligand-dependent domain is inactive, and ER co-activator binding is reduced by the TAM-ER complex; partial agonist activity results from the AF1 domain, which remains active in the TAM-ER complex [51] (Figure 2). …”
Section: Tamoxifen (Tam)mentioning
confidence: 99%